Cognitive sciences and variants: Commedia, Rime and the poetical works of Giacomo da Lentini - Di Veroli, Annamaria (Cognitive philology, 2017)
This paper is based on the fact that some variants or errors in the traditional versions of a work are attributable to the same cognitive processes that are involved in the process of copying. In order to evaluate the frequency with which this phenomenon occurs, we have conducted a statistical investigation of the variants and errors in the Italian manuscript traditions, in particular the Commedia and Rime of Dante Alighieri and the poetical works of Giacomo da Lentini, which are used as our sample or exemplars.